Bumble bee colony growth and reproduction depend on local flower dominance and natural habitat area in the surrounding landscape. (February 2017) - Spiesman, Brian J.; Bennett, Ashley; Isaacs, Rufus; Gratton, Claudio
Abstract: Conservation measures for bees often focus on increasing the diversity and abundance of floral resources. But it has not been clear if observed benefits of floral enhancements result from greater population growth, which is critical for the long-term success of conservation, or from mobile foragers aggregating in high-resource locations. Experimental evidence is only beginning to emerge in favor of the former mechanism and it is not well-established how different aspects of floral resources affect population growth. For example, bumble bee colonies may benefit from greater overall floral abundance, richness, or relative dominance of resource species. Because bumble bees are highly mobile, resource variability in the surrounding landscape is also important for colonies and may mediate local-scale effects. We experimentally assessed the growth and reproduction of bumble bee colonies ( Bombus impatiens ) deployed in grasslands in different local- and landscape-scale resource environments. We found that floral dominance, rather than the overall abundance or richness of floral resources, was the most important local factor for colony growth and reproduction. This may reflect more efficient foraging on a few numerically dominant and abundant resource species. Local- and landscape-scale predictor variables had interacting effects on colony growth and reproduction, suggesting that foraging distance depends on where in the landscape efficiently used resources are located. Our results provide further evidence that conservation strategies aimed at enhancing floral resources can increase bumble bee population growth. However, the most effective form of floral enhancement may vary among bee species. Graphical abstract: Highlights: Bumble bee colony growth reflected larger colonies with greater queen production. Colony growth increased with greater local floral dominance. Floral dominance predicted colony growth better than floral abundance or richness. Colony growth declined with greater natural habitat area in the adjacent landscape. Local- and landscape-scale environments had interacting effects on colony growth.